Entrepreneurship Education in Border As the realization of National Development and National Security - Yosua Damas Sadewo (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Entrepreneurship education in order to realize the national development has a role to create graduates who are competent in managing potential abundant natural resources. Resource management should be supported by an innovative and creative human resources. In this case the entrepreneurship education has a major role especially in support of national development in the border area. Besides a role in national development, entrepreneurship education in the border area also has a role to improve national resilience. As a form of national defense, education, entrepreneurial role in promoting education in the border region. In addition to the development of a walking area, people should have the spirit of nationalism in him. It is useful to filter out things that enter from neighboring countries, so that people be able to sort and reject the things that do not fit with the culture of the nation. nationalism spirit is a realization of national defense do society. Keywords: Entrepreneurship Education, National Development, and National Defense.